2017
DOI: 10.1002/cpe.4328
|View full text |Cite
|
Sign up to set email alerts
|

A quasi‐cache‐aware model for optimal domain partitioning in parallel geometric multigrid

Abstract: Summary Stencil computations form the heart of numerical simulations to solve Partial Differential Equations using Finite Difference, Finite Element, and Finite Volume methods. Geometric Multigrid is an optimal scriptOfalse(Nfalse), hierarchical tool employing stencil computations in its chief constituents, namely, smoothing, restriction, and interpolation. When Multigrid is parallelized over distributed‐shared memory architectures, traditionally, the domain partitioning creates cubic partitions of the mesh t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In [7] and [20] we formulated a strategy for minimizing the cache-misses of a sub-domain and showed the superiority of such partitions by experimenting on single grids and Geometric Multigrid, respectively . Overlap of communication with computation formed a significant part of our analytical derivation for cache-minimizing topologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7] and [20] we formulated a strategy for minimizing the cache-misses of a sub-domain and showed the superiority of such partitions by experimenting on single grids and Geometric Multigrid, respectively . Overlap of communication with computation formed a significant part of our analytical derivation for cache-minimizing topologies.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we tested our high level model for predicting optimal domain partitions on uniform structured 3-D grids developed in [7] and [20] for the more general cases of an AMR solver. The model in [7] demonstrated that communication minimization is not the sole criterion upon which mesh partitioning should be based and that it is essential to take into account the cache-misses for optimality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We initialize MPI with the MPI THREAD FUNNELED thread support level and after domain partitioning [27,28], assign the sub-domains to individual MPI processes. Our implementation as of now supports only a 1-D x-decomposition (see Appendix A).…”
Section: Internal Design and Domain Partitioningmentioning
confidence: 99%
“…Saxena et al provided a cost model that includes the traditional load‐balance between processors, the communication volume but also the cache misses to decompose optimally a matrix that may be 2D or 3D. The paper addresses a multi‐level decomposition, so that the model can take into account hybrid computers like a cluster of multi‐core computers.…”
Section: Hpc and Co: This Special Issuementioning
confidence: 99%